2016
DOI: 10.1159/000447816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Stress on Cognition in Male SAMP8 Mice

Abstract: Background/Aims: Chronic stress can lead to cognitive impairment. Senescence-accelerated mouse prone 8 (SAMP8) is a naturally occurring animal model that is useful for investigating the neurological mechanisms of Alzheimer's disease. Here we investigated the impact and mechanisms of chronic stress on cognition in male SAMP8 mice. Methods: Male 6-month- old SAMP8 and SAMR1 (senescence-accelerated mouse resistant 1) mice strains were randomly divided into 4 groups. Mice in the unpredictable chronic mild stress (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 55 publications
1
31
0
1
Order By: Relevance
“…Before our study, several studies reported that aging as chronic stress affect similarly hippocampus function as learning and memory (Tronche et al, 2010; Bonhomme et al, 2014; Wang et al, 2016), then we hypothesized that the modifications of hippocampus transcriptome induced by hypergravity should be similar to those observed in aged mice and/or mice treated with corticosterone.…”
Section: Discussionmentioning
confidence: 92%
“…Before our study, several studies reported that aging as chronic stress affect similarly hippocampus function as learning and memory (Tronche et al, 2010; Bonhomme et al, 2014; Wang et al, 2016), then we hypothesized that the modifications of hippocampus transcriptome induced by hypergravity should be similar to those observed in aged mice and/or mice treated with corticosterone.…”
Section: Discussionmentioning
confidence: 92%
“…The stressors included 1) food deprivation for 24 h, 2) water deprivation for 24 h with an empty bottle for the last 1 h, 3) overnight illumination, 4) removal sawdust for 24 h, 5) soiled cage (200 ml of water in 100 g of sawdust bedding) for 24 h, 6) forced swimming at 8 °C for 6 min, 7) tail nipping (1 cm from the tip of the tail), and 8) physical restraint for 2 h. Different stressors were applied in a pseudo-random manner each day, with the sequence of stressors changed weekly. The detailed process was shown in our previously paper [10]. …”
Section: Methodsmentioning
confidence: 99%
“…Many experiments have established that chronic stress is a risk factor for the development of cognitive deficits, especially for Alzheimer’s disease (AD). Chronic stress not only impaired the early long- term potentiation (LTP) in the at-risk rat model of AD [9], but it also decreased hippocampal synaptic plasticity [10] and increased amyloid-β plaque deposition in Tg2576 mice [11]. Furthermore, our previous study also confirmed that chronic stress exposure increased the levels of glucocorticoids (1.5-fold), promoted senile plaque deposition, neuronal injury, and cognitive impairment in APP/PS1 mice compared to wild-type mice [12]; however, the cognition-related metabolic mechanisms during chronic stress are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The MWM test was performed to evaluate the escape latency (the time to reach the hidden platform), travelled distance (the length of swim path) and time across the platform, as described in previous studies [19, 20]. Recognition tasks were performed as described previously [21].…”
Section: Methodsmentioning
confidence: 99%